The Effects of Transactions Costs on Labor Market Participation and Earnings: Evidence from Rural Philippine Markets - Leonardo A. Lanzona; Robert E. Evenson (Yale University, Economic Growth Center, 1997)
The paper aims to measure transaction costs and its effects on labor market participation and on wage earnings. The observed differences between between buying and selling prices of rice across households are used to calculate transaction costs indices for villages which are incorporated into the standard labor market participation and Mincer wage equations. The estimates indicate that transaction costs may be a source of the income differentials between (a) the landed and the landless, (b) the rural and the urban areas, and (c) the males and the females. Furthermore, biases can noted in the regression coefficients of estimates that do not control for transaction costs.
Keywords: 330; Transaction Costs; Labor Market Participation; Philippines; Ländlicher Arbeitsmarkt; Lohn; Transaktionskosten; Reismarkt; Philippinen